The Assessment of Natural Biomineral Leonardite on Growth and Pigmentation of Goldfish, Carassius auratus - Dilek Şahin; Meryem Öz; Ünal Öz (Life)
In this study, the impact of leonardite as a feed additive in goldfish diets was examined, focusing on its potential to positively influence feed and water parameters, which are critical for achieving sustainable ornamental fish farming. In this study, goldfish were fed diets containing four different levels of leonardite (0%, 2%, 6%, 10%). The experiment was conducted in 12 tanks with 3 replicates per treatment and lasted for 3 months. The fish, which were provided from the Research, Production and Training Institute, with an average live weight of 0.947 ± 0.03 g and an average length of 1.12 ± 0.02 cm, were used. After 90 days, it was observed that the specific growth rates increased in correlation with the amount of leonardite in the diet, with a statistically significant difference identified (p < 0.05). In this study, which investigated the coloration of fish with leonardite added to the feed for the first time, it was determined that the color of the fish approached from yellow to orange as the amount of leonardite added to the feed increased (p < 0.05). Given the positive effects observed on pigmentation and growth in this study, it is recommended that further detailed investigations be conducted on leonardite, a natural, harmless, and cost-effective additive, using different fish species.